2008
DOI: 10.1002/dneu.20626
|View full text |Cite
|
Sign up to set email alerts
|

Cux‐1 and Cux‐2 control the development of Reelin expressing cortical interneurons

Abstract: Homeodomain transcription factors play important roles in the specification and differentiation of neuronal subpopulations. In the cerebral cortex, the expression patterns of Cux-1 and Cux-2 in the medial ganglionic eminence (MGE) suggest a role for these transcription factors in the development of interneurons, a heterogeneous neuronal population. In this report, we describe expression of Cux-1 and Cux-2 proteins in Reelin-secreting interneurons of the cortical plate, but not in calretinin or parvalbumin subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
2
46
0
Order By: Relevance
“…4(G,N)]. In contrast, the distribution of Brn1, a transcription factor expressed by glutamatergic neurons of layers II-V (McEvilly et al, 2002;Sugitani et al, 2002), and Cux1, a marker for upper layer cortical neurons (Cubelos et al, 2008), revealed a decrease in the density of the upper layers and an increase in Cux1 and Brn1 positive cells in the lower layers of the Bmp7 null cortex as compared with wt [ Fig. 4(E,F,L,M)].…”
Section: Bmp7 Is Required For Proper CC Formationmentioning
confidence: 88%
“…4(G,N)]. In contrast, the distribution of Brn1, a transcription factor expressed by glutamatergic neurons of layers II-V (McEvilly et al, 2002;Sugitani et al, 2002), and Cux1, a marker for upper layer cortical neurons (Cubelos et al, 2008), revealed a decrease in the density of the upper layers and an increase in Cux1 and Brn1 positive cells in the lower layers of the Bmp7 null cortex as compared with wt [ Fig. 4(E,F,L,M)].…”
Section: Bmp7 Is Required For Proper CC Formationmentioning
confidence: 88%
“…4I). These genes include Cux2 and Lhx6, transcription factors previously shown to regulate interneuron migration and differentiation (26,30,32,33). Gad2 (Gad65), which encodes one of the key synthetic enzymes for the predominant cortical interneuron neurotransmitter GABA (34), is also diminished.…”
Section: Altered Interneuron Migration and Motility In The Embryonic mentioning
confidence: 99%
“…Similar to other extracellular signaling molecules, a critical locus of reelin signaling regulation is at the level of transcription (Erbel-Sieler et al, 2004; Wang et al, 2004; Chen et al, 2007; Miller and Sweatt, 2007; Cubelos et al, 2008), although receptor availability (Duit et al, 2010; Hong et al, 2010; Balmaceda et al, 2014) and secretion (Duveau et al, 2011) may also play a role. However, these mechanisms only serve to adjust the level of reelin signaling, as they are not sufficient to initiate the reelin signal by themselves.…”
Section: Introductionmentioning
confidence: 99%